Identifikasi Jenis Fioplankton di Tambak Udang Vannamei (Litopenaeus Vannamei) LSO AV3 Kecamatan Utan, Kabupaten Sumbawa - Yadi Putra Mansyah; Dwi Mardhia; Yudi Ahdiansyah (Indonesian Journal of Applied Science and Technology, 2020)
Phytoplankton play a very important role in a pond waters. Its ecological function as a primary producer and beginning of a chain in the food chain. The presence of phytoplankton in the waters can also describe the characteristics of a waters. The purpose of this study was to analyze the abundance, diversity, and uniformity of phytoplankton domination in the LSO AV3 pond, Utan District, Sumbawa Regency. This research has been carried out in Motong Village, Utan Subdistrict, Sumbawa Regency for 3 months from (January-March 2019) sampling using plankton net identification of phytoplankton species conducted at the AV3 LSO laboratory using a microscope then counted using a hand counter. In the research location, 4 classes were found, namely cyanophita, chloropyta, diatom and dinoflagellate. The highest abundance analysis of phytoplankton was in the chloropyta class with 22,720,000 (cell / ml) abundance, and the lowest was dinoflagellate with the lowest abundance of 5,140,000 cell / ml. , Diversity is with a value of 2.81 Uniformity that is with the amount of 0.80 and dominance is by the amount of 0.10.